Industry Attractiveness, Competitive Strategy and Company Performance in the Internet Service Provider in Indonesia - Hermina, Nurul; Haizam Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The development of information technology in this digital era is supposed to be a big opportunity for the internet service provider industry in Indonesia. However, the growth of the industry is not accompanied by an increase in the company’s income. Some companies are not able to survive due to very tight competition. High competition, while on the other hand the industry is still viewed as interesting, is considered the cause that makes internet service providers not able to continue their business. This research is aimed at evaluating the influence of competing strategies and industry attractiveness on the business performance of internet service providers in Indonesia. This research used primary data of 128 internet service providers in Indonesia that were collected through an online survey. By implementing the Partial Least Squares Modeling technique analysis, it was found out that competing strategy became the main factor influencing business performance compared to industry attractiveness. This finding is due to the fact that the internet industry remains an industry having a high level of attractiveness, but the main implication for management is how to make industry attractiveness able to improve company performance. With the right competitive strategy, companies will be able to survive in tight competition.